Folklore and Ethno-Rock Art Studies in the Kaimur Region of India: The Story of the Oraon Tribe. (8th June 2021) - Tiwary, Sachin Kumar; Dalai, Panchanan; Prakash, Om
The present work engages with a comparative study of the Oraon Folklore and their Rock Art for assessing how both these genres seemingly record the geo-cultural history of Oraon origin, their forced migrations and their current state of habitations in another Indian state Jharkhand. It attempts to establish a relation between archaeological data available in the form of rock art supplemented by written accounts and local traditions wherever possible. Based on field works, personal interactions with local inhabitants, especially on important events like, marriage, festivals, rituals etc., and archeological scrutiny of rock art available in the Oraons' previous habitation, i.e., the Kaimur Region in current Indian state of Bihar, the paper attempts to expose the historical value and cultural parallelism of Oraons' folk narratives and rock art. The paper strongly believes that both these genres conspicuously display the cultural history of a marginalized tribe that has undergone several historical and cultural ordeals. Besides this, the paper also offers, for the first time, an English translation of Oraons' oral folklore, adhering to the interdisciplinary approach of this paper. However, most significantly, the paper in its attempt to trace the continuity of rock art in this Kaimur Region also becomes an addition to the domain of ethno-rock art studies.